2012
DOI: 10.1108/01439911211268778
|View full text |Cite
|
Sign up to set email alerts
|

Motion control of walking assistant robot based on comfort

Abstract: Purpose -A walking assistant robot can help elderly people walk around independently, which could improve the life quality of the elderly and benefit our aging society. Ensuring the elderly person's walking comfort with such a robot is very important. At present, the majority of walking assistant robot research does not focus on this field. The purpose of this paper is to examine the requirements of comfortable walking and outline the design of a motion control algorithm for a walking assistant robot, Walkmate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…Specifically, ref. [ 47 ] implemented several motion control algorithms based on impulse force information. Moreover, this study evaluated the comfortableness of such control strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, ref. [ 47 ] implemented several motion control algorithms based on impulse force information. Moreover, this study evaluated the comfortableness of such control strategies.…”
Section: Discussionmentioning
confidence: 99%
“…Campbell () and Pfadenhauer and Dukat () have studied animal robots and concluded that they are suitable for care‐giving in general. Tang and Cao's () research on walking assistant robots adopts ideas that physical reinforcements will be implemented in everyday life in the near future.…”
Section: Discussionmentioning
confidence: 99%
“…Campbell (2011) and Pfadenhauer and Dukat (2015) have studied animal robots and concluded that they are suitable for care-giving in general. Tang and Cao's (2012) Jones, 2010). Nurses shown with, for example, the traditional nursing uniform often signal reliability and trustworthiness, but at the same time, the uniform also signals authority, competence and the ability to actively listen and establish trusting relationships.…”
Section: Discussionmentioning
confidence: 99%
“…Tang and Cao used force-sensing resistors to detect the pull or push pressure that the user poses on the handlebar of the robot. 13 Ye et al proposed a special arrangement of one-dimensional push-pull force sensors to measure the interactive force and torque between the human and the robot. 14 Jiang and Wang used four force sensors embedded in the armrest.…”
Section: Introductionmentioning
confidence: 99%
“…Admittance control algorithm and variant of admittance-based control algorithm are widely used in the walker robot. 4,7,8,10,11,13 Fuzzy control is also widely used. 12,15,18,22 Other control algorithms such as learning algorithm, 23 smooth control, 24 and Bayesian Networks mode 16 are also adopted to the walker robot.…”
Section: Introductionmentioning
confidence: 99%